Housework’s division in 24 European societies: a cross-national comparison - Voicu, Mălina; Voicu, Bogdan; Strapcova, Katarina (Calitatea Vieții, 2008)
The paper focuses on the factors which influence the sharing of domestic work in European countries. The prior studies have used as explanations the relative resources theory, the bargaining theory, the gender ideology or have combined them with some national features like welfare regime or gender equality, when predicting the housework’s division. We will compare the factors influencing the chores sharing in various European countries using regression models. The paper employs the ESS data, available for 24 European societies, and indicates that individual resources and gender ideology influence the dependent variable in most of investigated countries.